Correlation between the trajectory of systolic blood pressure and new renal damage in a nonhypertensive population. Issue 5 (October 2017) - Wang, Zhi-Jun; Jia, Dao; Tian, Jun; Liu, Jie; Li, Li-Jie; Huang, Yu-Ling; Cao, Xin-Ying; Ning, Chun-Hong; Zhao, Quan-Hui; Yu, Jun-Xing; Zhang, Rui-Ying; Zhang, Ya-Jing; et al.
Abstract : Objective: This study aims to investigate the correlation between the trajectory of systolic blood pressure (SBP) and new renal damage in a nonhypertensive population. Patients and methods: This prospective cohort study included a total of 14 382 nonhypertensive individuals, employees of Kailuan Group of Companies, who took part in five healthy examinations in 2006–2007, 2008–2009, 2010–2011, 2012–2013, and 2014–2015, and had complete data. These individuals were divided into four groups according to the different trajectories of SBP: low–low, low–stable, middle–high, and high–high groups. The correlation between the trajectory of SBP and new renal damage in a nonhypertensive population was analyzed using a multivariate Cox's proportional hazard regression model. Results: (a) A total of 14 382 individuals had complete data and the average age of these individuals was 44.6±10.8 years. Among these, 10 888 (75.7%) individuals were men and 3494 (24.3%) individuals were women. (b) These individuals were divided into four groups according to different trajectories of blood pressure: low–low group, accounting for 13.15% (blood pressure was <106 mmHg); low–stable group, accounting for 53.91% (blood pressure was between 115 and 116 mmHg); middle–high group, accounting for 28.77% (blood pressure was between 125 and 131 mmHg); and high–high group, accounting for 4.6% (blood pressure was between 126 and 151 mmHg). (c) With the increase in the trajectory of SBP, the detection rate of renal damage increased gradually. From the low–low group to the high–high group, the detection rates of estimated glomerular filtration rate (eGFR) less than 60 ml/min/1.73 m 2 were 2.3, 2.4, 3.6, and 4.3%, respectively; the positive rates of urinary protein were 1.7, 2.9, 3.8, and 5.5%, respectively; and the detection rates of eGFR less than 60 ml/min/1.73 m 2 or positive urinary protein were 4, 5.2, 7.3, and 9.3%, respectively ( P <0.05). (d) After adjustment for other confounding factors, multivariate Cox's proportional hazard regression analysis showed that compared with the low–low group, the risk of eGFR less than 60 ml/min/1.73 m 2 increased by nearly 1.5 times in the high–high group and in the low–stable, middle–high, and high–high groups, the risks of positive urinary protein, eGFR less than 60 ml/min/1.73 m 2, or positive urinary protein increased by 1.48–2.34 and 1.20–1.70 times, respectively. Conclusion: In a nonhypertensive population, the high trajectory of SBP is a risk factor for kidney damage. Abstract : Supplemental Digital Content is available in the text.